2016
DOI: 10.1590/s0100-204x2016000500019
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de clones de braquiária para resistência à lagarta-do-cartucho

Abstract: Resumo -O objetivo deste trabalho foi avaliar e selecionar clones de braquiária (Urochloa ruziziensis) resistentes à lagarta-do-cartucho, Spodoptera frugiperda (Lepidoptera: Noctuidae), para uso em sistema de integração lavoura-pecuária-floresta. Foram avaliados 147 clones de U. ruziziensis em delineamento inteiramente casualizado, com três repetições. Como testemunha e padrão de suscetibilidade, foi utilizada uma dieta artificial adequada ao desenvolvimento do inseto. Folhas dos diferentes clones de U. ruzizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Different species of the genus Brachiaria spp. were good hosts for S. frugiperda, allowing the complete development of this insect (Auad et al, 2016). Thus, selecting plants that minimize the biotic potential of this insect pest is one of the challenges in intercropped plantations in the CLI.…”
Section: Resultsmentioning
confidence: 99%
“…Different species of the genus Brachiaria spp. were good hosts for S. frugiperda, allowing the complete development of this insect (Auad et al, 2016). Thus, selecting plants that minimize the biotic potential of this insect pest is one of the challenges in intercropped plantations in the CLI.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, forage crops are cultivated for other purposes. Species such as Bermuda grass (Cynodon dactylon) are commonly used as a "green bridge" in the off-season (Ribeiro et al 2020), or in integrated crop-livestock systems where green forage is used for animal feed (Auad et al 2016). As far as we are aware, published studies have addressed only the contribution of alternative host species to the maintenance of pest populations in the eld during the crop season (Ribeiro et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on forage lines resistance attributes (levels, types, and mechanisms of resistance) to lepidopterous pest species (Lynch et al 1981, Wiseman & Duncan 1996, Braman & Duncan 2000, Auad et al 2016. However, to date, there are no reports comparing fall armyworm development and adaptability on forage species and row crops largely cultivated in Brazil (i.e., corn and soybean).…”
Section: Discussionmentioning
confidence: 99%
“…Caterpillars (Lepidoptera) are potential pests of pastures capable of consuming rapidly large productive areas worldwide (Auad et al 2016). Despite their seasonal occurrence, caterpillars exhibit great voracity, especially for their ability to scrape and consume leaves, reducing forage availability and pasture support capacity (Ribeiro & Castilhos 2018).…”
Section: Introductionmentioning
confidence: 99%